2000
DOI: 10.2307/3454516
|View full text |Cite
|
Sign up to set email alerts
|

PCB Congener Profile in the Serum of Humans Consuming Great Lakes Fish

Abstract: The State of Michigan has a long history of research into human exposure to environmental contaminants through consumption of recreationally caught fish. A large cohort of Lake Michigan residents who eat fish (fish-eaters) and those who do not eat fish (nonfish-eaters) established in 1980 served as the basis for the congener-specific polychlorinated biphenyl (PCB) exposure evaluation reported here. In this paper we present the serum PCB congener profile for a subset of this cohort who were over 50 years of age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
31
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 16 publications
4
31
1
Order By: Relevance
“…Blood samples were collected by phlebotomist field staff and analyzed by the MDPH, using the Webb-McCall packed-column gas chromatography analytic method to quantify total serum PCBs in all samples collected from the cohort (Hovinga et al 1992(Hovinga et al , 1993Humphrey 1983;Schantz et al 1996); congener-specific analyses were carried out only on the samples collected during the last survey (Humphrey et al 2000). The limit of detection for total PCBs in serum was 3 ppb throughout the study period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blood samples were collected by phlebotomist field staff and analyzed by the MDPH, using the Webb-McCall packed-column gas chromatography analytic method to quantify total serum PCBs in all samples collected from the cohort (Hovinga et al 1992(Hovinga et al , 1993Humphrey 1983;Schantz et al 1996); congener-specific analyses were carried out only on the samples collected during the last survey (Humphrey et al 2000). The limit of detection for total PCBs in serum was 3 ppb throughout the study period.…”
Section: Methodsmentioning
confidence: 99%
“…From 1980 to 1982, the MDPH established a cohort of 572 fisheaters and 419 non-fisheaters [the Michigan Fisheater (MFE) Cohort] to evaluate the potential for human exposure to environmental contaminants through consumption of Lake Michigan sport-caught fish (Humphrey 1983). Detailed information regarding the MFE Cohort has been described previously (Hovinga et al 1992(Hovinga et al , 1993Humphrey 1983Humphrey , 1992Humphrey and Budd 1996;Humphrey et al 2000). Briefly, fisheaters were selected based on the amount of sport-caught fish consumed [≄ 26 lb/year] and compared with randomly selected age-, sex-, and region-matched "non-fisheaters" who consumed < 6 lb of sport-caught fish per year.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, findings from a cohort of older participants (≄ 50 years of age in 1992) recently demonstrated that a reduction in current fish consumption was associated with a monotonic decline in PCB levels in blood serum (Tee 2003). Although self-reported fish consumption has substantially declined over time, sport-caught fish intake continues to be one of the key predictors of serum PCB levels Humphrey et al 2000;Tee 2003 breast milk, or adipose tissue in various populations (Dallaire et al 2002;Fitzgerald et al 1999;Hovinga et al 1992;Konishi et al 2001;Noren and Meironyte 2000;Robinson et al 1990;Smith 1999). According to Noren and Meironyte (2000), the level of organochlorine compounds in 1997 was approximately one-tenth of the 1972 level in breast milk from Swedish mothers living in the Stockholm region.…”
Section: Discussionmentioning
confidence: 76%
“…The level of PCBs in serum sampled from a general population of men and women in Michigan significantly declined from 1979 to 1989 (Humphrey et al 2000); however, levels remained virtually unchanged in sport-caught fish consumers. In contrast, findings from a cohort of older participants (≄ 50 years of age in 1992) recently demonstrated that a reduction in current fish consumption was associated with a monotonic decline in PCB levels in blood serum (Tee 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Even though the production of PCBs was banned in 1976 in the United States, there is still great concern about the potential toxic effects of PCBs that have been released into the environment. Recent investigations showed that human populations with a high fish consumption have considerably higher concentrations of PCBs and PCB metabolites in their tissues than control populations (2)(3)(4).…”
mentioning
confidence: 99%